Penerapan Algoritma Fisher-Yates Shuffle pada Computer Based Test Ujian Sekolah di SMKN 1 Payung - Rendy Rian Chrisna Putra; Tri Sugihartono (Universitas Bumigora, 2019)
The school exam aims to measure the success of the teaching and learning process, whether students are able to accept the material taught and whether the teacher is able to provide the material properly and correctly. In the era of the current technological era, SMKN 1 Payung already uses CBT (Computer Based Test) technology in the implementation of school examinations, the advantages of using CBT are paperless, and the results of the exam can be seen immediately after the exam, the disadvantage is the possibility of students cheating like cheating can still happen. To overcome this weakness, a problem randomization algorithm is applied, namely the Fisher-Yates Shuffle algorithm. By using the Fisher-Yates Shuffle algorithm, the sequence of questions received by each student while carrying out this CBT-based school exam will be different, thereby reducing the indication of students to cheat. In the results of the study, testing is done using blackbox testing to test whether the software functionality is functioning properly. The results of the implementation and testing that are applied prove that using of the Fisher-Yates Shuffle algorithm can help overcome the weaknesses in computer-based tests (CBT) in SMKN 1 Payung.